SARS-CoV-2 and Emerging Variants: Unmasking Structure, Function, Infection, and Immune Escape Mechanisms - Li, Jiaqi; Jia, Huimin; Tian, Miaomiao; Wu, Nijin; Yang, Xia; Qi, Jianni; Ren, Wanhua; Li, Feifei; Bian, Hongjun (Frontiers in Cellular and Infection Microbiology, 2022)
As of April 1, 2022, over 468 million COVID-19 cases and over 6 million deaths have been confirmed globally. Unlike the common coronavirus, SARS-CoV-2 has highly contagious and attracted a high level of concern worldwide. Through the analysis of SARS-CoV-2 structural, non-structural, and accessory proteins, we can gain a deeper understanding of structure-function relationships, viral infection mechanisms, and viable strategies for antiviral therapy. Angiotensin-converting enzyme 2 (ACE2) is the first widely acknowledged SARS-CoV-2 receptor, but researches have shown that there are additional co-receptors that can facilitate the entry of SARS-CoV-2 to infect humans. We have performed an in-depth review of published papers, searching for co-receptors or other auxiliary membrane proteins that enhance viral infection, and analyzing pertinent pathogenic mechanisms. The genome, and especially the spike gene, undergoes mutations at an abnormally high frequency during virus replication and/or when it is transmitted from one individual to another. We summarized the main mutant strains currently circulating global, and elaborated the structural feature for increased infectivity and immune evasion of variants. Meanwhile, the principal purpose of the review is to update information on the COVID-19 outbreak. Many countries have novel findings on the early stage of the epidemic, and accruing evidence has rewritten the timeline of the outbreak, triggering new thinking about the origin and spread of COVID-19. It is anticipated that this can provide further insights for future research and global epidemic prevention and control.